Value Co-Creation in Sports Events : CASE: Yonoton - Ruohisto, Matti (My University, 2018)
Sports industry and sports events evolve continuously. Event organizers need to be able to find new ways to adding value to different actors. Thus co-operation becomes important. One way to understand the complex nature of adding value in sports field is to look at it through the principles of value co-creation. Therefore the main objective of this study is to provide insights into value co-creation in sports industry. This is executed by investigating value co-creation in sports events in Finland. In addition to this, one of the objectives is to provide a deeper understanding of what and how different patterns and processes are involved when co-creating value in sports events in Finland. As this study seeks to get an understanding of a specific phenomenon it is conducted as a single case study. The research adapts qualitative and exploratory research methods. The case company investigated is Yonoton Limited. Yonoton Limited provides a mobile application enabling value co-creation within various actors. The application operates as a platform for different actors in sports events enabling them to for example optimize resources, offer in-seat deliveries and deliveries to fast lanes when making purchases. The empirical part of this research constitutes of two semi-structured and one structured qualitative interviews with four different stakeholders. In order to add strength to the study, also field observation was conducted. In the end this study poses one main research question: “How is value co-created in sports events?” and five sub-questions: “What different actors are involved when using Yonoton?”, “How users & non-users benefit from Yonoton?”, “What characterizes the co-operation surrounding Yonoton?”, “How are services exchanged when utilizing Yonoton?” and “How institutions shape the processes when utilizing Yonoton?” The results suggest that value co-creation in sports events should be investigated more. Value co-creation constitutes of a set of processes that have an impact in various actors. Different direct and indirect factors such as institutions influence in many ways shaping how people behave in events. Yonoton could therefore be a useful tool enabling value co-creation in this field. This research emphasizes that it is important for actors to understand how value could be co-created and on the other hand what could cause value destruction. In the end this research provides grounds for future research. It is suggested that also research in value co-destruction should be conducted.
Keywords: Yonoton Limited, Yonoton, value, value co-creation, sports industry, sports events, Yonoton Oy, arvo, arvon yhteisluonti, urheilutoimiala, urheilutapahtumat